Dynamic rayed aurora and enhanced ion-acoustic radar echoes - Blixt, E. M.; Grydeland, T.; Ivchenko, N.; Hagfors, T.; La Hoz, C.; Lanchester, B. S.; Løvhaug, U. P.; Trondsen, T. S. (Annales Geophysicae, 2005)
The generation mechanism for naturally enhanced ion-acoustic echoes is still debated. One important issue is how these enhancements are related to auroral activity. All events of enhanced ion-acoustic echoes observed simultaneously with the EISCAT Svalbard Radar (ESR) and with high-resolution narrow field-of-view auroral imagers have been collected and studied. Characteristic of all the events is the appearance of very dynamic rayed aurora, and some of the intrinsic features of these auroral displays are identified. Several of these identified features are directly related to the presence of low energy (10-100eV) precipitating electrons in addition to the higher energy population producing most of the associated light. The low energy contribution is vital for the formation of the enhanced ion-acoustic echoes. We argue that this type of aurora is sufficient for the generation of naturally enhanced ion-acoustic echoes. In one event two imagers were used to observe the auroral rays simultaneously, one from the radar site and one 7km away. The data from these imagers shows that the auroral rays and the strong backscattering filaments (where the enhanced echoes are produced) are located on the same field line, which is in contrast to earlier statements in the litterature that they should be separated.